Factors Underlying Marijuana Use: A Case Study of a Criminal Court Decision - Shidqi Rivandra (Estudiante Law Journal, 2026)
Technological and societal developments have generated significant benefits for modern society; however, they have also contributed to increasingly complex forms of criminal activity, including narcotics-related offenses. In Indonesia, the development and circulation of narcotics have been influenced by technological advancement, which has facilitated new methods of communication, distribution, and illicit transactions. The growing prevalence of narcotics abuse, as reflected in numerous cases investigated and prosecuted by law enforcement authorities, has become a serious concern due to its implications for public health, social order, and criminal justice. Narcotics and other addictive substances constitute not merely a domestic problem but also a transnational challenge, particularly because their production, distribution, and consumption frequently involve networks operating across national borders. In response, states have adopted various measures to prevent and combat the illicit trafficking and abuse of narcotics through international and regional cooperation, as well as through the enactment of specific domestic legislation. Nevertheless, the strict prohibition of certain narcotics also raises legal concerns when substances classified as prohibited narcotics possess potential therapeutic benefits. This article examines the regulation of Class I narcotics in Indonesia, particularly marijuana, in relation to their potential use for medical purposes. By examining the existing legal framework and developments concerning the therapeutic use of cannabis, this article argues for a more proportional and evidence-based approach to narcotics policy. In particular, it emphasizes the importance of scientific research and regulatory reform to accommodate the controlled medical use of certain narcotic substances while maintaining strict safeguards against abuse and illicit distribution